Efikasi Diri Guru: (Studi Di Kabupaten Sidenreng Rappang - Sulawesi Selatan) - Minarni, Minarni (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
Education is a milestone in civilization change, thus human resources are needed to make this change. The human resources in mention are teachers or educators. Teachers are human beings who play an important role in being able to educate the life of the nation and state. Teachers are mandatory to mastering skills, intellect, and competence in dealing with all problems in tasks either are easy or difficult. In the context of teacher education has an important role in making change. There are many things that need to be conducted, it thus requires skills. One of the things that can be seen from the ability of teachers to improve the quality and effectiveness of teaching is self-efficacy. Self-efficacy is a belief which provides experience to individuals in doing and achieving something. Self-efficacy is only a small part of the picture of human activities in life. This study uses quantitative research methods using research instruments in the form of self-efficacy. The technique of collecting data used in this study is non-probability sampling, namely purposive sampling. The sample in this study were 280 people consisting of junior high school teachers from various schools in the district of Sidrap. The measuring instrument used in this study is a self-efficacy scale based on the Bandura theory. The technique of data analysis used in this research is descriptive statistics. The results showed that the description of the level of teacher knowledge in Sidenreng Rappang Regency was in the medium category with the proportion of 38.29%.